HUBUNGAN PAPARAN XYLENE DAN METHYL HIPPURIC ACID PADA PEKERJA INFORMAL PENGECATAN MOBIL DI KARASAK, BANDUNG - Gede Herang Cahyana (CR JOURNAL (CREATIVE RESEARCH FOR WEST JAVA DEVELOPMENT), 2015)
Xylene (dimetilbenzene) is a derivative of benzene with molecul formula C6H4(CH3)2 and grouped to aromaticorganic compound with high toxicity. Xylene is widely used as a paint solvent, often inhaled by workers whichcan cause health problems both acute and chronic. Methyl Hippuric Acid (MHA) is a result of xyleneprocessing by human body, then excreted in urine after passing through several processes. On observation ofworkshop workers with questionnaire was found that there were some exposure data at every time theyworked: 0.042 to 4.447 ppm. By reference to the regulation of Labor and Transmigration Minister No.13/2011,the concentration of xylene found not exceed the threshold limit value 100 ppm. The TLV is 100 ppm. Theresults showed a relationship between xylene and MHA was a fairly strong with the value of r (correlation)0.813. Concluded, greater concentration of xylene would increase MHA concentration so the workshop’sworkers could be expressed as exposed to xylene. The workers have to use masks to prevent theirselvesfrom another toxic chemicals in paints. The results could be used by West Java and Bandung CityGovernment to release regulation to prevent informal workers in car workshop and people from xylene risk.